Carbon cycling in the Sargasso Sea water column: Insights from lipid biomarkers in suspended particles. (November 2018) - Pedrosa-Pàmies, R.; Conte, M.H.; Weber, J.C.; Johnson, R.
Highlights: Lipids reveal seasonal and depth changes in suspended particle organic composition. Rapid evolution in suspended carbon composition in upper mesopelagic zone. Particle composition in deep ocean and nepheloid layer linked to surface production. Lipids reveal depth evolution of deep ocean microbial communities. Physical forcing by extreme storms (hurricanes) impacts deep ocean particle cycle. Abstract: This study compares lipid biomarker and bulk constituents (organic carbon and δ 13 C, nitrogen and carbonate) in particles (30–4400 m depth) collected at the Oceanic Flux Program site in the northern Sargasso Sea off Bermuda during three periods of contrasting oceanographic conditions: following the spring bloom (April 2015), during the low productivity period (November 2015), and two weeks after the passage of the Category 3 Hurricane Nicole (October 2016). Lipids biomarkers were used to evaluate the contributions of phytoplankton, zooplankton and bacterial sources to the particulate organic carbon (POC), diagenetic transformations of suspended POC throughout the water column and within the nepheloid layer, and seasonal and non-seasonal temporal variability, including the impact of an extreme weather event. Depth profiles of lipid concentration and molecular composition showed seasonal and non-seasonal variability in particle composition throughout the water column. Higher lipid concentrations in April versus November 2015 reflected differences in plankton productivity, while relative abundances in diagnostic phytosterols, C18 polyunsaturated fatty acids and alkenones reflected differences in phytoplankton community structure. A rapid decrease in lipid biomarker concentrations below the euphotic zone was accompanied by a marked transition in lipid composition, e.g. increases in the relative percentages of cholesterol, C16 -C18 fatty alcohols, odd- and branched- chain fatty acids. This reveals the intense remineralization of algal-derived carbon and fresh inputs of organic materials from zooplankton and microbial production within the upper mesopelagic zone. Particulate lipids within the bathypelagic zone reveal a close connectivity of deep particulate carbon composition with upper ocean properties, while compositional heterogeneity with depth reflects continuous particle turnover and de novo particle production throughout the deep water column. Additionally, depth trends in the within-class composition of fatty alcohols and bacterial fatty acids were observed, suggesting depth zonation of zooplankton and microbial community structure. Hurricane Nicole (October 2016) strongly impacted upper ocean physics and nutrient supply, resulting in a transient phytoplankton bloom/flux event that increased concentrations of fresh particulate phytodetritus (e.g., C18 polyunsaturated fatty acids) throughout the mesopelagic and upper bathypelagic zones. Concurrent increases in zooplankton and bacterial lipid biomarkers (e.g., 18:1ω9, odd- and branched-chain fatty acids, cholesterol) indicated that this transient pulse of labile carbon stimulated mesopelagic zooplankton and microbial activity, resulting in an enrichment of labile materials in the suspended particle pool throughout the deep ocean. Our study demonstrates that extreme weather events can have a major impact on carbon flux and particle cycling in the deep ocean, with pronounced implications for the ocean carbon pump and deep ocean ecosystems.